Basupera a feasibility study on reverse vending machines in the Philippines - Castillo, Adrian Paulo; Gorospe, Samantha Trinidad; Santos, Earl Jan; Valdez, Cyle Vincent
The reverse vending machine has helped revolutionize segregation, and rewards this act of segregation with not only money, but different rewards as well, catering to the marketing needs of its different sponsors. Currently, there are more than 100,000 machines deployed worldwide. The study aims to determine if such a product, Basupera machines, would be feasible in the Philippine setting. Manila produces 25% of the total garbage generated in the Philippines, and Quezon City has the highest. budget for waste management amounting to one billion pesos to collect 700,000 tons of its trash per year. In Quezon City, PET contributes to about 1.87% of total trash generated. Even though this seems to be a small proportion, it still amounts to 12,406,994 kg per year. Metro Manila's recycling rate has slowed down significantly with a rate of 25% in 2002 to a rate of 31% in 2009. There has also been a steady increase in Quezon City's population of 3% and an average annual increase of 4% in million units sold of PET bottles, resulting to more trash generated. Given the unique reward system that the machine incorporates, the use of these machines would be very attractive in the country. The study first aims ta put the Basupera machines in schools and malls, as these locations would prove to be most applicable, ,considering bottle consumption, foot traffic, education benefits, and security. The proponents have designed the Basupera machine based on reverse vending machines abroad. Basically, what the system does is to take in PET bottles, and convert them into rewards, in this case, points that could be converted to various items or donations to several institutions, as deemed by the user. The non-profit organization would circle around three revenue schemes as its business model. First and foremost, being a non-profit organization, grants and contributions would be one major source of revenue. Secondly, the organization would gain revenues by selling the collected bottles of the machines. Bottles would be collected from the machines based on a schedule and would be brought to the recycling center.The Basupera machines would not be sold, as the organization would like it to act as an automated satellite recycling machine. Lastly, revenue would be generated from advertising. Exterior surfaces of the Basupera machines could be rented as advertisement space, given material to be placed are appropriate. The proponents have also determined that outsourcing is the best model for assembly of the machines compared to in-house assembly or importing as it presented lower production costs. This is mainly due to the low forecasted production of machines. A small organization was considered to be sufficient for its operations. Based on the financial statements forecasted, the organization would have positive net cash flows at the end of each year, for the five year period. Based on the income statement, a positive net income will be realized starting the second year of operations. A high positive net present value was then determined, indicating that the project is very desirable. Given the goals of the project, and the support of the Quezon City government, contributions or grants are expected to be received by the organization. These funds would play a big part in financing the study, as this would be recognized from several sources like the Green Fund, and from other private and public institutions. The Basupera project is also a new alternative that hopefully would promote recycling and waste management, by engaging citizens through its rewards system. It has been determined by the proponents that with this kind of recycling system, the project could potentially collect 1,193 tons of PET bottles for its first 5 years of implementation. This is equivalent to saving about 2,328,666.90 Php for the government in trash collection, Php 14,368,939 of oil savings and Php 36, 870, 064.66 worth of energy as compared to when using wgin materials for PET bottle production. Considering these, the project also has a high positive net present value when it tomes to social profitability.